O homem da pena de aço: Monteiro Lobato e a articulação da raça na educação republicana - Costa, Fabio Pereira (2016)
In the last decades of the nineteenth century and in the beginning of the twentieth century, a range of intellectuals believed that technical knowledge such as medicine, engineering and education pointed outputs for the racial problems in Brazil. A relevant name in this scenario is the scholar José (Bento) Monteiro Lobato (1882-1948) who during the first decades of the twentieth century joined intellectuals interested in enabling the issues from childhood and education, permeated by racial debates, on Revista do Brasil (1918-1925), on Revista da Sociedade de Educação (1923-1924) and, in a peculiar way, in his own literature. Then, in order to clarify this facet of Lobato’s trajectory, it is pointed out the historical issue: what is the role of the writer and editor Monteiro Lobato towards the process of providing texts and intellectuals who disseminated a republican educational project, which was based on the racial discussions? The aim of this paper was, through Culture of Social History, to reassemble on the context of the Brazilian republican historical process the social interlocutions, the debate about culture and people, using the experiences from the scholars and the social identities built and performed. The study revealed a preponderant participation of Lobato on the educational writers’ organization on the periodicals, which were under his command, and in the way such discussion was present in his literature.